3D printing polymer precursor bionic cuttlebone ceramic scaffold as well as preparation method and application thereof
By combining polymer precursor strategies with 3D printing technology, a porous magnesium feldspar scaffold with bionic cuttlefish bone structure was prepared, which solved the problem of the microstructure of the existing ceramic scaffolds being non-dense and insufficient mechanical properties, and achieved high compressive strength and promoting bone repair.
Patent Information
- Application Number
- CN202411671859.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-04
AI Technical Summary
The existing 3D printed ceramic stent has not dense microstructure, insufficient mechanical strength, and the porous structure is inconsistent with the mechanical properties, resulting in poor mechanical properties, limiting its application in bone tissue engineering.
A porous magnesium feldspar scaffold with bionic cuttle bone structure was prepared using polymer precursor strategy and 3D printing technology. The magnesium feldspar phase is generated through the sintering process, which improves the compactness and compressive strength of the stent.
The dense microstructure and high compressive strength of the ceramic scaffold are realized, the mechanical properties of the scaffold are improved, and the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells are promoted, and the effect of bone defect repair is enhanced.
Smart Images

Figure CN119551977A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bioceramic material preparation, and in particular relates to a 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold and a preparation method and application thereof. Background Art
[0002] In the field of bone tissue engineering, silicate bioceramics are considered to be a promising alternative to bone repair materials due to their good biocompatibility and bioactivity. Studies have shown that constructing appropriate porous structure bioceramic materials is beneficial to enhancing the osteogenesis and vascularization of biomaterials. In recent years, three-dimensional (3D) printing technology has shown unique advantages in constructing complex structures and has been widely used to manufacture bioceramic scaffolds. Various 3D printed bioceramic scaffolds with designed porous structures have been developed, showing good biological properties. In addition to good biological properties, scaffolds should also provide appropriate strength to avoid fracture during implantation and support the defect site in the early stage. However, the microstructure of 3D printed ceramic scaffolds is not dense, and the porous structure of ceramic scaffolds is inconsistent with mechanical strength. Therefore, most 3D printed porous bioceramic scaffolds have poor mechanical properties, which increases the difficulty of surgical operations and greatly affects their scope of application.
[0003] The polymer-derived ceramic (PDC) strategy, where ceramics are derived from pre-ceramic polymer precursors, is becoming a powerful alternative to traditional ceramic synthesis and manufacturing techniques. The PDC strategy combined with 3D printing technology can prepare ceramic scaffolds with dense microstructures and enhanced mechanical strength, which suggests that introducing the PDC strategy to fabricate 3D printed bioceramic scaffolds may be an effective strategy to improve the compressive strength of porous scaffolds.
[0004] Furthermore, inspired by the relationship between the hierarchical structure and high strength of natural materials, many biomimetic materials with enhanced mechanical strength have been developed by imitating the structure of natural materials such as bone, nacre or crab shell. Cuttlebone (CUTT) is the rigid skeleton of cuttlefish that can withstand multiple stresses (hydrostatic pressure and shear stress) during complex movements, which requires cuttlebone to withstand extreme external water pressure of up to 60 atmospheres and avoid the occurrence of damage, which means that cuttlebone must be both hard and damage-resistant. Studies have shown that the special thin-sheet diaphragms and S-shaped walls of cuttlebone play a crucial role in its excellent mechanical properties. In addition, compared with other plate-based porous materials, cuttlebone-structured porous synthetic materials also exhibit lighter weight, higher strength and more effective energy absorption. Summary of the invention
[0005] In view of the above technical problems, the purpose of the present invention is to manufacture a porous magnesia chalcite scaffold (PDC / CUTT-AKT) with a cuttlefish bone-like structure by combining the PDC strategy with bionic manufacturing based on 3D printing technology. Benefiting from the polymer precursor strategy and the bionic cuttlefish bone structure, its microstructure is more compact and the compressive strength is greatly improved. In addition, the scaffold can promote the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells and promote the repair of bone defects.
[0006] In a first aspect, the present invention provides a method for preparing a 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold, the preparation method comprising the following steps: (1) mixing a polymer precursor with a photosensitive resin to obtain a printing paste; (2) using 3D modeling software to design a support structure as a bionic cuttlefish bone structure, and performing 3D printing on the printed slurry, and performing cleaning and secondary curing after printing to obtain a bionic cuttlefish bone ceramic support blank; (3) Sintering the bionic cuttlefish bone ceramic scaffold blank to generate a chemical reaction to generate a magnesia feldspar phase, thereby obtaining the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold.
[0007] Preferably, in step (1), the polymer precursor comprises H44 silicone resin, calcium oxide, magnesium oxide and N,N-dimethylformamide; Preferably, the molar ratio of Si, Ca and Mg elements in the polymer precursor is controlled to be 1:1:(0.3-0.7), preferably 1:1:0.5.
[0008] Preferably, in step (1), the mass ratio of the polymer precursor to the photosensitive resin is (1-2):1.
[0009] Preferably, in step (1), the mixing method is planetary ball milling, and the ball milling mixing time is 1-5 hours, preferably 3 hours.
[0010] Preferably, in step (2), the process parameters of the 3D printing include: a printing layer thickness of 25-75 um, preferably 50 um; an exposure time of 2-5 s, preferably 3 s.
[0011] Preferably, in step (2), the cleaning is performed using anhydrous ethanol; and the secondary curing is performed under a light source of 405 nm.
[0012] Preferably, in step (3), the sintering is carried out in a tubular furnace in an argon atmosphere; the heating rate is 0.5-2°C / min; the temperature is kept at 100-200°C for 1-3h, preferably at 150°C for 2h; the temperature is kept at 600-700°C for 2-5h, preferably at 650°C for 3h; the temperature is kept at 1300-1400°C for 1-5h, preferably at 1400°C for 3h.
[0013] In a second aspect, the present invention provides a 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold obtained according to the above preparation method.
[0014] Preferably, the main phase of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold is magnesia chalcite phase Ca2MgSi2O7, with a mass percentage of more than 50%, preferably 50%-100%; the porosity is 50-53%; the compressive strength reaches 23.3-40MPa; the residual mass after immersion in Tris-HCl with pH = 7.2-7.4 for 25-30 days is 88-92wt%, the Ca, Mg and Si ion release concentrations are 25-27ppm, 8-10ppm and 7-9ppm respectively, and the final pH value of the solution is 8.6-8.8.
[0015] In a third aspect, the present invention provides an application of the above-mentioned 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold in the preparation of bone defect repair materials.
[0016] Beneficial Effects (1) The 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold prepared by the present invention has a dense microstructure. Thanks to this dense microstructure, the scaffold has both high porosity and high compressive strength. Compared with other structures, the cuttlefish bone-like structure can further improve the compressive strength of the scaffold, thereby effectively improving the mechanical properties of the scaffold. (2) The bioactive ion release rate and pH value of the ceramic scaffold provided by the present invention are lower than those of conventional AKT scaffolds, and the ceramic scaffold has good in vitro biocompatibility, can promote cell adhesion, proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells, and has broad prospects in clinical application in bone defect repair; (3) The present invention provides a new strategy for improving the mechanical properties of bioceramic scaffolds. The designed CUTT structure is a scaffold model with both excellent mechanical strength and osteogenic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The preparation process and structure and performance schematic diagram of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold exemplified in the present invention; Figure 2 , 3The micro-CT images, surface SEM images, and cross-sectional SEM images of the stents prepared in Example 1 and Comparative Examples 1-3 are shown respectively; Figure 4 Schematic diagram of the compressive strength of ceramic brackets with different sintering temperatures and structures prepared in Examples 1-3 and Comparative Examples 1-2 and 5-8; Figure 5 Schematic diagram of the data showing the mass loss (a), pH value of the extract (b), and cumulative amount of ion release (ce) of the ceramic stents prepared in Example 1 and Comparative Examples 1-4 after being immersed in Tris-HCl for different time periods; Figure 6 Live-dead staining images (a) and adhesion confocal images (b) of bone marrow mesenchymal stem cells cultured using the ceramic scaffolds prepared in Example 1 and Comparative Examples 1-4; Figure 7 Cell proliferation (a), osteogenic-related gene expression (bf) and 3D CLSM distribution images (gi) of the ceramic scaffolds prepared in Example 1 and Comparative Examples 1-4 when bone marrow mesenchymal stem cells were cultured, where gi are Comparative Example 1, Comparative Example 2 and Example 1, respectively; Figure 8 This is an H&E staining image of the repair effect of the ceramic scaffold prepared in Example 1 on skull defects; Figure 9-10 These are low-magnification and high-magnification images of Masson staining showing the repair effect of the ceramic scaffold prepared in Example 1 on skull defects. DETAILED DESCRIPTION
[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0019] First, combine Figure 1 , exemplarily illustrating the preparation method of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold provided by the present invention. The preparation method may include the following steps: (1) mixing a polymer precursor with a photosensitive resin to obtain a printing paste; (2) using 3D modeling software to design a support structure as a bionic cuttlefish bone structure, and performing 3D printing on the printed slurry, and performing cleaning and secondary curing after printing to obtain a bionic cuttlefish bone ceramic support blank; (3) Sintering the bionic cuttlefish bone ceramic scaffold blank, generating a chemical reaction during the sintering process to generate a magnesia chalcite phase, and obtaining the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold.
[0020] The preparation method adopted by the present invention is a polymer precursor method, that is, the ceramic slurry used in printing is not the corresponding ceramic powder slurry, but the precursor of the corresponding ceramic powder, which can react during the sintering process to generate the final corresponding ceramic phase. The present invention combines the PDC strategy with 3D printing technology to prepare a ceramic bracket with a dense microstructure and enhanced mechanical strength.
[0021] In some embodiments, in step (1), the polymer precursor may include H44 silicone resin, calcium oxide, magnesium oxide and N,N-dimethylformamide; preferably, the molar ratio of Si, Ca and Mg elements in the polymer precursor may be controlled to be 1:1:(0.3-0.7), preferably 1:1:0.5. By controlling the molar ratio of the three elements to the above ratio, sufficient magnesia chalcedony phase (AKT, Ca2MgSi2O7) can be promoted in the ceramic after subsequent sintering, and at the same time, the appropriate microenvironmental pH value can be ensured after the ceramic stent is implanted in the organism.
[0022] Wherein, the mass proportion of the N,N-dimethylformamide may be 5-15% of the total mass of the polymer precursor.
[0023] In some embodiments, in step (1), the mass ratio of the polymer precursor to the photosensitive resin can be (1-2): 1. The photosensitive resin is mainly used for 3D printing and will be removed during the subsequent sintering process. If the relative amount of the polymer precursor is too large, it will lead to the inability to form by the photocuring method; if the relative amount is too small, it will cause the ceramic to break during the sintering process.
[0024] In some embodiments, in step (1), the mixing method can be planetary ball milling, and the ball milling mixing time can be 1-5 hours, preferably 3 hours.
[0025] In some embodiments, in step (2), the process parameters of the 3D printing may include: a printing layer thickness of 25-75 um, preferably 50 um; an exposure time of 2-5 s, preferably 3 s.
[0026] The thickness of the printed layer is related to the exposure time. The thicker the layer, the longer the exposure time required. If the layer thickness is too high, powder will fall off during the printing process, and the printer resolution will limit the layer thickness to a lower level. In addition, the design of the bracket of the present invention is a cuttlefish bone-like structure. Photocuring printing can achieve the construction of the structure in the simplest way. Other printing methods generally have difficulty in constructing a fine cuttlefish bone-like structure.
[0027] In some embodiments, in step (2), the cleaning may be performed using anhydrous ethanol.
[0028] In some embodiments, in step (2), the secondary curing can be performed under a light source of 405 nm.
[0029] In some embodiments, in step (3), the sintering can be carried out in a tubular furnace in an argon atmosphere; the heating rate can be 0.5-2°C / min; 100-200°C for 1-3h, preferably 150°C for 2h; 600-700°C for 2-5h, preferably 650°C for 3h; 1300-1400°C for 1-5h, preferably 1400°C for 3h.
[0030] Among them, the sintering must go through two steps of eliminating organic matter and sintering of inorganic matter. The elimination of organic matter is divided into two stages, namely, the elimination of N,N-dimethylformamide at a temperature of 100-200°C and the elimination of photosensitive resin at 600-700°C. The first two sintering temperatures are used to remove organic matter. If the temperature is too high here, the organic matter will be eliminated too quickly, the bracket will shrink faster, and the ceramic will break; if the temperature is too low, the removal time will increase, or even the organic matter cannot be removed. The final sintering temperature is the temperature required for the formation of the magnesia feldspar phase. If the temperature is too high, it will easily cause the bracket to melt, and if the temperature is too low, the ceramic phase cannot be obtained. In addition, too short a holding time is not conducive to the reaction, and too long a holding time will waste time.
[0031] The main phase of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold obtained by the above-mentioned preparation method provided by the present invention is magnesia chalcite phase (AKT, Ca2MgSi2O7), with a mass proportion of more than 50%, preferably 50%-100%; it has a dense microstructure, and the porosity can be 50-53%; the compressive strength can reach 23.3-40MPa; the residual mass after soaking in Tris-HCl with pH = 7.2-7.4 (such as pH = 7.4) for 25-30 days (such as 28 days) is 88-92wt%, the Ca, Mg and Si ion release concentrations are 25-27ppm, 8-10ppm and 7-9ppm respectively, and the final pH value of the solution is 8.6-8.8.
[0032] In summary, the present invention combines PDC and 3D printing technology to prepare a ceramic scaffold with a dense microstructure and enhanced mechanical properties through 3D printing of polymer precursors. In addition, inspired by the structure of natural cuttlefish bones, this study designed the 3D printed scaffold into a bionic cuttlefish bone structure and prepared a 3D printed polymer precursor bionic cuttlefish bone AKT ceramic scaffold. AKT is a bioactive ceramic that has received widespread attention in tissue engineering. The present invention uses silicone resin, calcium oxide, and silicon oxide as element sources, and prepares a bionic cuttlefish bone ceramic scaffold through 3D printing. The raw material generates an AKT phase in situ during the sintering process, and the microstructure is denser and the mechanical properties are more superior.
[0033] In addition, the ceramic scaffold provided by the present invention has good mechanical properties and degradability as well as good biocompatibility and biological activity, has a good promoting effect on the adhesion, proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells, has a good effect on promoting the repair of bone defects, can be used as a bone tissue implant that meets clinical requirements, and is used in the preparation of bone defect repair materials.
[0034] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0035] Example 1
[0036] The preparation method of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold (PDC / CUTT-AKT) provided in this embodiment comprises the following steps: (1) 30 g H44 silicone resin (source: Wacker Chemie Co., Ltd.), 14.7 g calcium oxide, 5.25 g magnesium oxide, 5.63 g N,N-dimethylformamide and 38 g photosensitive resin were mixed and ball-milled in a planetary ball mill at a speed of 500 rpm for 3 h to obtain a printing slurry; (2) Designing a bionic cuttlefish bone structure using Unigraphics NX and adjusting the structural parameters; first, slicing the obtained STL format file through the printer program and then importing it into the printer; then, pouring the printing slurry prepared in step (1) into the material box of the light-curing printer, setting the printing thickness of each layer to 50 μm, and the exposure time of each layer to 3 s, and printing; after printing, removing the sample and placing it in anhydrous ethanol for ultrasonic cleaning for 2 minutes to remove uncured resin, and repeating the cleaning step three times; then, placing the cleaned ceramic green body bracket under a portable 405 nm light source for secondary curing for 3 hours to obtain a bionic cuttlefish bone ceramic bracket blank; (3) Sintering the bionic cuttlefish bone ceramic scaffold blank prepared in step (2) in a tubular furnace protected by an argon atmosphere, wherein the sintering process is as follows: increasing the temperature from room temperature to 150°C at a rate of 0.5°C / min and keeping the temperature for 2 hours to ensure that N,N-dimethylformamide is completely removed; then, increasing the temperature to 650°C at a rate of 1°C / min and keeping the temperature for 3 hours to ensure that the photosensitive resin is completely decomposed; finally, increasing the temperature to 1400°C at a rate of 2°C / min and keeping the temperature for 3 hours to obtain the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold.
[0037] The mechanical properties, degradation properties and biological properties of the 3D printed polymer precursor bionic cuttlebone ceramic scaffold prepared in Example 1 were evaluated, and it was found that the compressive strength was 35.8 MPa; the residual mass after immersion in Tris-HCl at pH = 7.4 for 28 days was 90.55%, the released concentrations of Ca, Si and Mg ions were 26.2 ppm, 8.1 ppm and 8.2 ppm respectively, and the final pH value of the solution was 8.68.
[0038] Example 2
[0039] The preparation method of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold (PDC / CUTT-AKT-1350) provided in this embodiment refers to Example 1, with the main differences being: In step (3), the maximum sintering temperature is 1350°C.
[0040] The mechanical properties of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold prepared in Example 2 were evaluated, and it was found that the compressive strength was 28.9 MPa.
[0041] Example 3
[0042] The preparation method of the 3D printed polymer precursor bionic cuttlebone ceramic scaffold (PDC / CUTT-AKT-1300) provided in this embodiment refers to Example 1, with the main differences being: In step (3), the maximum sintering temperature is 1300°C.
[0043] The mechanical properties of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold prepared in Example 3 were evaluated, and it was found that the compressive strength was 23.3 MPa.
[0044] Comparative Example 1
[0045] The preparation method of the 3D printed polymer precursor staggered structure ceramic scaffold (PDC / INT-AKT) provided in this comparative example refers to Example 1, with the main differences being: In step (2), the bionic cuttlebone structure is replaced by a staggered structure.
[0046] The mechanical properties, degradation properties and biological properties of the 3D printed polymer precursor interlaced structure ceramic scaffold prepared in Comparative Example 1 were evaluated, and the results showed that the compressive strength was 19.1 MPa, the residual mass after immersion in Tris-HCl at pH = 7.4 for 28 days was 92.23%, the released concentrations of Ca, Si and Mg ions were 22.7 ppm, 7.0 ppm and 7.2 ppm respectively, and the final pH value of the solution was 8.65.
[0047] Comparative Example 2
[0048] The preparation method of the 3D printed polymer precursor octagonal truss structure ceramic bracket (PDC / OCT-AKT) provided in this comparative example refers to Example 1, with the main differences being: In step (2), the bionic cuttlefish bone structure is replaced by an octagonal truss structure.
[0049] The mechanical properties, degradation properties and biological properties of the 3D printed polymer precursor octagonal truss structure ceramic scaffold prepared in Comparative Example 2 were evaluated, and the results showed that the compressive strength was 20.7 MPa, the residual mass after immersion in Tris-HCl with pH = 7.4 for 28 days was 90.79%, the released concentrations of Ca, Si and Mg ions were 25.7 ppm, 8.1 ppm and 8.1 ppm respectively, and the final pH value of the solution was 8.76.
[0050] Comparative Example 3
[0051] The preparation method of the 3D printed staggered structure ceramic bracket (INT-AKT or AKT) provided in this comparative example refers to Example 1, with the main differences being: The slurry preparation step in step (1) is as follows: 45 g of magnesia chalcedony powder and 55 g of photosensitive resin are mixed and ball-milled in a planetary ball mill at a speed of 500 rpm for 3 h to obtain a printing slurry; In step (2), the bionic cuttlebone structure is replaced with a staggered structure; The sintering step of step (3) is as follows: the green body bracket obtained by the 3D printing ceramic powder slurry method is placed in a muffle furnace, the temperature is raised from room temperature to 650°C at a rate of 1°C / min, and kept at this temperature for 3 hours; then the temperature is raised to 1350°C at a rate of 2°C / min and sintered for 3 hours.
[0052] The mechanical properties, degradation properties and biological properties of the 3D printed polymer interlaced structure ceramic scaffold prepared in Comparative Example 3 were evaluated, and the results showed that the compressive strength was 20.5 MPa, the residual mass after immersion in Tris-HCl at pH = 7.4 for 28 days was 87.61%, the released concentrations of Ca, Si and Mg ions were 32.3 ppm, 10.0 ppm and 10.1 ppm respectively, and the final pH value of the solution was 9.05.
[0053] Comparative Example 4
[0054] The preparation method of the 3D printed staggered structure ceramic bracket (INT-TCP or TCP) provided in this comparative example refers to Example 1, with the main differences being: The slurry preparation step in step (1) is as follows: 45 g TCP (tricalcium phosphate) powder and 55 g photosensitive resin are mixed and ball-milled in a planetary ball mill at a speed of 500 rpm for 3 h to obtain a printing slurry; In step (2), the bionic cuttlebone structure is replaced with a staggered structure; The sintering step of step (3) is as follows: the green body bracket obtained by the 3D printing ceramic powder slurry method is placed in a muffle furnace, the temperature is raised from room temperature to 650°C at a rate of 1°C / min, and kept at this temperature for 3 hours; then the temperature is raised to 1350°C at a rate of 2°C / min and sintered for 3 hours.
[0055] The mechanical properties, degradation properties and biological properties of the 3D printed polymer interlaced structure TCP ceramic scaffold prepared in Comparative Example 4 were evaluated, and it was found that the residual mass after immersion in Tris-HCl at pH = 7.4 for 28 days was 95.69%, the release concentration of Ca ions was 2.7 ppm, and the final pH value of the solution was 7.72.
[0056] Comparative Example 5
[0057] The preparation method of the 3D printed polymer precursor staggered structure ceramic bracket (PDC / INT-AKT-1350) provided in this comparative example refers to comparative example 1, with the main differences being: In step (3), the maximum sintering temperature is 1350°C.
[0058] The mechanical properties of the 3D printed polymer precursor staggered structure ceramic bracket prepared in Comparative Example 5 were evaluated, and it was found that the compressive strength was 13.5 MPa.
[0059] Comparative Example 6
[0060] The preparation method of the 3D printed polymer precursor staggered structure ceramic bracket (PDC / INT-AKT-1330) provided in this comparative example refers to comparative example 1, the main difference is: In step (3), the maximum sintering temperature is 1300°C.
[0061] The mechanical properties of the 3D printed polymer precursor staggered structure ceramic bracket prepared in Comparative Example 6 were evaluated, and it was found that the compressive strength was 9.9 MPa.
[0062] Comparative Example 7
[0063] The preparation method of the 3D printed polymer precursor octagonal truss structure ceramic bracket (PDC / OCT-AKT-1350) provided in this comparative example refers to comparative example 2, with the main differences being: In step (3), the maximum sintering temperature is 1350°C.
[0064] The mechanical properties of the 3D printed polymer precursor octagonal truss structure ceramic bracket prepared in Comparative Example 7 were evaluated, and it was found that the compressive strength was 13.9 MPa.
[0065] Comparative Example 8
[0066] The preparation method of the 3D printed polymer precursor octagonal truss structure ceramic bracket (PDC / OCT-AKT-1300) provided in this comparative example refers to comparative example 2, with the main differences being: In step (3), the maximum sintering temperature is 1300°C.
[0067] The mechanical properties of the 3D printed polymer precursor octagonal truss structure ceramic bracket prepared in Comparative Example 8 were evaluated, and it was found that the compressive strength was 10.3 MPa.
[0068] Comparative Example 9
[0069] The preparation method of the 3D printed polymer precursor bionic cuttlebone ceramic scaffold (PDC / CUTT-AKT-low magnesium) provided in this comparative example is the same as that in Example 1, except that: In step (1), the amount of magnesium oxide used is 3 g.
[0070] The degradation performance of the ceramic prepared in Comparative Example 9 was directly evaluated, and it was found that the pH value after being immersed in Tris-HCl for 1 day was 10.5. Such a high pH value would seriously affect the activity of cells.
[0071] Figure 2 , 3 The micro-CT images, surface SEM images, and cross-sectional SEM images of the stents prepared in Example 1 and Comparative Examples 1-3 are shown respectively. From the surface morphology of the conventional AKT stent without PDC strategy, there are obvious cracks and large pores on the surface and cross section of the stent ( Figure 2(a2)-(a4)); In contrast, each type of PDC-AKT scaffold has a dense microstructure with no cracks on the surface ( Figure 2 (b2)-(d4)); Although the cross-section of the PDC-AKT scaffold still exhibits some pores, the size and number of pores in the PDC-AKT scaffold struts are much smaller than those in the conventional AKT scaffold ( Figure 3 ), compared with the traditional 3D printing and sintering techniques, the introduction of the PDC strategy is obviously beneficial to the preparation of 3D Akt scaffolds with dense microstructures, which may further enhance the mechanical properties of the scaffolds.
[0072] Figure 4 The compressive strength diagram of the ceramic brackets with different sintering temperatures and different structures prepared in Examples 1-3, Comparative Examples 1-2, and 5-8. It can be seen from the figure that as the temperature increases, the compressive strength of the bracket increases accordingly; in addition, compared with the staggered structure and the octagonal truss structure, the compressive strength of the bionic cuttlefish bone bracket is higher.
[0073] Figure 5 The data schematic diagram of the mass loss (a), pH value of the extract (b), and cumulative ion release (ce) of the ceramic scaffolds prepared in Example 1 and Comparative Examples 1-4 after soaking in Tris-HCl for different time periods. It can be seen from the figure that compared with the TCP scaffold, the AKT and PDC-AKT scaffolds exhibited higher degradation rates and sustained release of Mg and Si bioactive ions, and the degradation rate of the PDC-AKT scaffolds with three different structures was slower than that of the AKT scaffold, which may be due to the dense microstructure of the scaffold.
[0074] Next, bone marrow mesenchymal stem cells were inoculated on the samples for culture, and the effects of the prepared ceramic scaffolds on cell adhesion, proliferation, and expression of osteogenesis-related genes were studied.
[0075] The Transwell experiment was used to investigate the effect of ion release from the scaffold on the activity of rBMSCs. A 24-well plate with a chamber was used, and the scaffold was placed in the upper chamber. 4cells) were planted in the lower chamber; then, 1 mL of culture medium was added to each well to completely submerge the scaffold; after incubation for 24 h, the Calcein-AM / PI double staining kit (Dojindo, Japan) was diluted with phosphate-buffered saline (PBS) at a volume ratio of PBS:AM:PI=1000:2:3; the specific process was as follows: first, the chamber and scaffold were removed, the 24-well plate was rinsed twice with PBS, and then the live / dead staining working solution was added; after incubation at 37°C for 25 min, fluorescent images were taken using a confocal laser scanning microscope (FV1000, Olympus, Japan); live cells were stained green and excited with a 488 nm laser; dead cells were stained red and excited with a 559 nm laser.
[0076] For the cell adhesion experiment, the sealed bottom scaffolds were placed in a 48-well plate, and 50 μL of rBMSCs concentrate (2×10 6 Cells / mL, 1×10 per scaffold 5 cells), and 400 μL of culture medium was added along the wall of the well to keep the scaffold moist; the scaffold was then incubated for 4 h to ensure complete cell attachment; then 400 μL of culture medium was added to each well to completely submerge the scaffold; after 24 h of incubation, the culture medium was aspirated using a vacuum pump, the cell-loaded scaffold was fixed with paraformaldehyde solution for 1 h, FITC staining solution (Sigma-Aldrich, USA) was added to stain the cytoskeleton, and then PBS was added to wash three times, and DAPI (Sigma-Aldrich, USA) was added to stain the cell nucleus for 10 min; finally, the scaffold was rinsed three times with PBS and the cell adhesion was observed under a single-photon laser confocal microscopy system (TCS SP8, Leica, Germany); in addition, continuous images of each structure were taken under a single-photon laser confocal microscopy system (CLSM) with a vertical interval of 2 μm per image, and finally merged into a three-dimensional CLSM image to reflect the cell distribution and number on each structural unit.
[0077] For the cell proliferation experiment, the sealed bottom scaffolds were placed in a 48-well plate, and 50 μL of rBMSCs concentrate (2×10 6 Cells / mL, 1×10 per scaffold 5cells), and 400 μL of culture medium was added along the wall of the well to keep the scaffold moist; after incubating the scaffold for 4 h to ensure complete attachment of the cells, 400 μL of culture medium was added to each well to completely submerge the scaffold; the culture medium was replaced every 2 days, and the same number of cells were colonized in the empty wells as a control; on days 1, 3, and 7, the culture medium was replaced with 800 μL of working solution containing 10% CCK-8, and after culturing for 2.5 h, 100 μL of working solution was aspirated from each well in a 96-well plate under light-proof conditions, and the absorbance of the solution was measured at an excitation wavelength of 450 nm in an automatic microplate reader (SpectraFluor Plus, Tecan, Germany) (n=4).
[0078] For gene expression testing, the scaffolds were placed in a 48-well plate and 50 μL of rBMSCs concentrate (2 × 10 6 Cells / mL, 1×10 per scaffold 5 Cells) and 400 μL of culture medium was added along the well wall to keep the scaffold moist; the scaffold was then incubated for 4 h to ensure complete cell attachment; the culture medium was then sucked dry with a vacuum pump, and 10 scaffolds in each group were transferred to a 6-well plate and completely submerged with 5 mL of culture medium. After 7 days of culture in an incubator, total RNA was extracted using Trizol reagent (Thermal Fisher, USA); cDNA was prepared using PrimeScript First-Strand cDNA Synthesis Kit (TOYOBO, Japan); RT-PCR experiments were performed using SYBR Green QPCR Master Mix (TaKaRa, Japan), with GADPH as an endogenous control and 2 -ΔΔCt The calculation was performed using the method (n=3).
[0079] Figure 6 Live-dead staining images (a) and adhesion confocal images (b) of bone marrow mesenchymal stem cell culture using ceramic scaffolds prepared in Example 1 and Comparative Examples 1-4. Live-dead staining results show that rBMSCs are well distributed in the PDC-AKT group and present an active morphology with abundant pseudopodia; confocal images show that rBMSCs with typical cytoskeletal morphology are densely and evenly distributed on the pillars of all scaffolds; these results indicate that all bioceramic scaffolds have suitable rBMSCs attachment sites, which are conducive to promoting cell migration and proliferation.
[0080] Figure 7 Cell proliferation (a), osteogenic-related gene expression (bf) and 3D CLSM distribution images (gi) of the cells when bone marrow mesenchymal stem cells were cultured in the ceramic scaffolds prepared in Example 1 and Comparative Examples 1-4, where gi is Comparative Example 1, Comparative Example 2 and Example 1, respectively. Figure 7As can be seen in (a), the PDC / OCT-AKT and PDC / CUTT-AKT groups showed significantly higher cell proliferation values at 3 and 7 days. In addition, the osteogenic differentiation of rBMSCs on different scaffolds was evaluated; Figure 7 As shown in (b)-(f), the expression levels of most genes in the PDC-AKT group were much higher than those in the BLANK group. Previous studies have also shown that appropriately released bioactive ions and pH values can effectively stimulate the adhesion and further growth of rBMSCs, but excessive or insufficient ions hinder the adhesion and growth of rBMSCs. Compared with the TCP group, the PDC-AKT scaffold not only provides additional bioactive Mg ions, but also has a lower release rate and pH value of bioactive ions than the AKT group, which may be the main reason for the better expression of cell proliferation, adhesion and osteogenic genes in the PDC-AKT group. Figure 7 (g)-(i) show that rBMSCs adhered to the oblique walls of the OCT and CUTT structures, while there was no obvious cell adhesion on the vertical wall of the INT structure, which is consistent with the results of cell proliferation.
[0081] Figure 8 This is an H&E staining image of the repair effect of the ceramic scaffold prepared in Example 1 on skull defects. The results show that a large amount of new bone tissue appears around the material.
[0082] Figure 9-10 The Masson staining low-power and high-power images of the skull defect repair effect of the ceramic scaffold prepared in Example 1. The results show that there is regeneration of collagen tissue around the material, and the above results indicate that the material can promote the repair of bone defects in vivo.
[0083] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold, characterized in that: The preparation method comprises the following steps: (1) mixing a polymer precursor with a photosensitive resin to obtain a printing paste; (2) using 3D modeling software to design a support structure as a bionic cuttlefish bone structure, and performing 3D printing on the printed slurry, and performing cleaning and secondary curing after printing to obtain a bionic cuttlefish bone ceramic support blank; (3) Sintering the bionic cuttlefish bone ceramic scaffold blank to generate a chemical reaction to generate a magnesia feldspar phase, thereby obtaining the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold.
2. The preparation method according to claim 1, characterized in that: In step (1), the polymer precursor includes H44 silicone resin, calcium oxide, magnesium oxide and N,N-dimethylformamide; Preferably, the molar ratio of Si, Ca and Mg elements in the polymer precursor is controlled to be 1:1:(0.3-0.7), preferably 1:1:0.
5.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the mass ratio of the polymer precursor to the photosensitive resin is (1-2):
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step (1), the mixing method is planetary ball milling, and the ball milling time is 1-5 hours, preferably 3 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), the process parameters of the 3D printing include: a printing layer thickness of 25-75 um, preferably 50 um; an exposure time of 2-5 s, preferably 3 s.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the cleaning is performed using anhydrous ethanol; and the secondary curing is performed under a light source of 405 nm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the sintering is carried out in a tubular furnace in an argon atmosphere; the heating rate is 0.5-2°C / min; the temperature is kept at 100-200°C for 1-3h, preferably at 150°C for 2h; the temperature is kept at 600-700°C for 2-5h, preferably at 650°C for 3h; the temperature is kept at 1300-1400°C for 1-5h, preferably at 1400°C for 3h.
8. A 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold obtained by the preparation method according to any one of claims 1 to 7.
9. The 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold according to claim 8, characterized in that: The main phase of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold is magnesia chalcite phase Ca2MgSi2O7, which accounts for more than 50% by mass, preferably 50%-100%; the porosity is 50-53%; the compressive strength reaches 23.3-40MPa; the residual mass after soaking in Tris-HCl with pH = 7.2-7.4 for 25-30 days is 88-92wt%, the Ca, Mg and Si ion release concentrations are 25-27ppm, 8-10ppm and 7-9ppm respectively, and the final pH value of the solution is 8.6-8.
8.
10. Use of the 3D printed polymer precursor bionic cuttlefish bone ceramic scaffold according to claim 8 or 9 in the preparation of bone defect repair materials.